Perbandingan Penilaian Kinerja Reksadana Saham Konvensional dan Syariah Dengan Metode Treynor dan Sharpe - Sari Mujiani; Rizki Sakinah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2019)
Mutual Fund's performance is very good if able to provide a higher-level rate of return and reduce risk, and will be better performance as a market of comparison (benchmark). This research aims to provide comparison performance conventional mutual fund shares and mutual fund shares shari'a in Indonesia. There are 48 conventional mutual fund shares and 7 mutual fund shares shari'a is sample research. Samples taking method used is purposive sampling. Types of this research is descriptive quantitative by using this method Treynor and Sharpe. The type of data that is used is secondary data (NAV) that to sample is data 2012 until 2014. Analysis techniques that the used data is Independent Samples T-test. Mutual Fund shares have good performance when more than the ratio Treynor and Sharpe, the better performance mutual fund shares. The result of this research is that there is no difference between performance conventional mutual fund shares with the performance (IHSG) using the market Treynor method with the values the significance > a (0.367 > 0.05) and Sharpe (0.820 > 0.05). To performance mutual fund shares shari'a, there is no difference by using this method Treynor > a (0.703 > 0.05) while Sharpe there are differences that significantly between performance shari'a mutual fund shares with the performance market (JII) to the significance < a (0.006 < 0.05). While there are no differences between performance mutual fund shares with conventional shari'a mutual fund use methods Treynor > a (0.499 > 0.05) and Sharpe (0.112 > 0.05). Mutual fund shares And conventional better (outperformance) of mutual fund shares shari'a